2014
DOI: 10.1016/j.jtcvs.2013.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusions are associated with urinary biomarkers of kidney injury in cardiac surgery

Abstract: Objective Cardiac surgery is a major cause of acute kidney injury. In this setting receipt of blood transfusions appears to associate with a higher risk of AKI, as measured using serum creatinine values. We examined this association further, using urinary biomarkers of kidney injury. Methods 1210 adults underwent cardiac surgery and were divided into three groups based on the receipt of intraoperative packed red blood cell units (PRBC): no blood (n=894), ≤ 2 PRBC (n=206) and > 2 PRBC (n=110). AKI was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 31 publications
(42 reference statements)
6
37
1
2
Order By: Relevance
“…We observed a higher frequency of coronary heart disease, hypertension, and diabetes mellitus among men, suggesting that these factors may contribute to some extent to men being more likely than women to experience AKI. Our data revealed that RBC transfusion during surgery was an independent risk factor for AKI, which was in agreement with the findings of previous studies (24). However, although RBC transfusion was found to be associated with a high risk of AKI, the “ideal” transfusion thresholds in cardiac patients remain largely unknown (25).…”
Section: Discussionsupporting
confidence: 93%
“…We observed a higher frequency of coronary heart disease, hypertension, and diabetes mellitus among men, suggesting that these factors may contribute to some extent to men being more likely than women to experience AKI. Our data revealed that RBC transfusion during surgery was an independent risk factor for AKI, which was in agreement with the findings of previous studies (24). However, although RBC transfusion was found to be associated with a high risk of AKI, the “ideal” transfusion thresholds in cardiac patients remain largely unknown (25).…”
Section: Discussionsupporting
confidence: 93%
“…This stands in contrast to recent data in cardiac surgery suggesting that blood products can be associated with AKI [32,33] and that urinary AKI biomarkers are also associated with AKI [34]. Our investigation, however, examined significantly more detailed perioperative and postoperative interventions than these studies, and the possibility remains that unmeasured confounders related to patient care may cloud the blood product-AKI relationship.…”
Section: Commentmentioning
confidence: 59%
“…Karkouti (144) identified 20 observational studies showing an association between transfusion of packed red blood cells and AKI (and 1 study that found no difference). Since that time, additional studies have added to the growing body of literature suggesting that anemia and the use of packed red blood cells are independent risk factors for AKI after cardiac surgery (145)(146)(147). Catalytic iron (i.e., circulating iron not bound to any proteins) can produce hydroxyl radicals, cause oxidative tissue damage, and has been proposed as a nephrotoxin (148).…”
Section: Perioperative Transfusion Of Packed Red Blood Cellsmentioning
confidence: 99%